The Influence of Cognitive Skills on the Core Values of Science Class Students - Libed, Glenda (JPAIR Multidisciplinary Research, 2017)
The Philippines has felt the need of brilliant leaders that would impact growth and development of the country. Thus, this study determined the influence of cognitive skills on the core values of students. Specifically, it aimed to determine: 1) respondents’ characteristics considering self-awareness, stress - coping skills, self - motivation, environmental influences such as family, peer and media; and academic performance; 2) students’ cognitive skills; 3) level of students’ core values; 4) difference in the students’ cognitive skills and core values when grouped according to their characteristics; and 5) extent of contribution of the students’ cognitive skills on their core values. This descriptive research used simple random sampling method, descriptive and inferential statistics. Results showed that students have good stress coping skills, self-motivation, family and peer relationships. Their overall cognitive skills and core values are fair and good, respectively. Students with good family and peer influence, high academic performance have significantly higher cognitive skills and core values. Their cognitive skills also positively affect core values. There is hope for a much better performance as they are rated good in core values given that the respondents are still grade 9. With proper intervention, they could assume leadership roles and be highly competitive leaders.